2017
DOI: 10.1073/pnas.1702688114
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative time-resolved chemoproteomics reveals that stable O -GlcNAc regulates box C/D snoRNP biogenesis

Abstract: -linked GlcNAcylation (-GlcNAcylation), a ubiquitous posttranslational modification on intracellular proteins, is dynamically regulated in cells. To analyze the turnover dynamics of -GlcNAcylated proteins, we developed a quantitative time-resolved-linked GlcNAc proteomics (qTOP) strategy based on metabolic pulse-chase labeling with an -GlcNAc chemical reporter and stable isotope labeling with amino acids in cell culture (SILAC). Applying qTOP, we quantified the turnover rates of 533-GlcNAcylated proteins in NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 73 publications
(79 reference statements)
2
66
0
Order By: Relevance
“…Chemoproteomic profiling identified hundreds to thousands of modified proteins for each unnatural sugar (Figure S8 A and Table S5) as well as hundreds of cysteine sites modified with un‐, mono‐, di‐, or triacetylated unnatural sugars (Figure A, Figure S8 B and Table S6). Based on the analysis of the Ac 4 GlcNAz‐treated lysates using a resolvable mass tag, the stoichiometry of the S‐glycosylation of the two proteins GAPDH and AK2 was estimated to be about 22 % and 25 %, respectively (Figure B). Ac 4 GlcNAz labeling in lysates was abolished by adding Ac 4 GlcNAc, which indicates that the nonspecific S‐glycosylation was independent of the azido group (Figure S9 A).…”
Section: Figurementioning
confidence: 99%
“…Chemoproteomic profiling identified hundreds to thousands of modified proteins for each unnatural sugar (Figure S8 A and Table S5) as well as hundreds of cysteine sites modified with un‐, mono‐, di‐, or triacetylated unnatural sugars (Figure A, Figure S8 B and Table S6). Based on the analysis of the Ac 4 GlcNAz‐treated lysates using a resolvable mass tag, the stoichiometry of the S‐glycosylation of the two proteins GAPDH and AK2 was estimated to be about 22 % and 25 %, respectively (Figure B). Ac 4 GlcNAz labeling in lysates was abolished by adding Ac 4 GlcNAc, which indicates that the nonspecific S‐glycosylation was independent of the azido group (Figure S9 A).…”
Section: Figurementioning
confidence: 99%
“…Since O-GlcNAcylation was first reported, more than one thousand proteins have been shown to be O-GlcNAcylated. O-GlcNAcylation affects diverse cellular and molecular processes, including protein-protein interactions, transcriptional regulation, autophagy, cell proliferation and apoptosis, and insulin sensitivity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many signaling processes act at short time scales. Because compounds that rapidly and specifically reduce O-GlcNAc through inhibition of OGT were not available until recently, studies that interrogate OGT function have primarily focused on changes that occur long after an initial perturbation has been applied (∼24-48 h) (16,17). Much has been learned about OGT, but the long time frame of typical studies is a limitation: some of the observed pathway changes may be downstream of the initial changes, and important effects may have been missed due to compensatory changes that occur prior to interrogation.…”
Section: Introductionmentioning
confidence: 99%